The Effectiveness of Using English Speaking Club to Improve Speaking Skill ini Maritime Faculty of Ivet University - Wibowo, Rahmat Ari (Marine Science and Technology Journal, 2022)
Nowadays English is very important for us. Basically, the development of the four skills is integrated, but some of people think that speaking is the most difficult one. Research questions of this research are: Does English Speaking Club improves the students’ speaking ability? and What are the effects of English Speaking Club for the students?. Objectives of the research are: 1. To investigate whether the speaking club improves the students’ speaking ability, 2. To find out the effect of English Speaking Club for the students. For statement number 1, activities in English Speaking Club can increase self-confidence for the students. There are 55 respondents (55%) and 23 respondents (23%) who strongly agree and agree and no one choose disagree or strongly disagree. We can conclude that activities in speaking club are effective in increasing confident, especially in speaking skill. Based on the results of the interview data and questionnaire of the research, we can conclude that English Speaking Club can improve the students’ speaking ability.